The Euler’s harmonic holomorphic regenerative universe - Horia DUMITRESCU; Vladimir CARDOS; Radu BOGATEANU (INCAS Bulletin, 2024)
The Cartesian dualism is a precursor to Euler’s complex theory, that completes the Descartes-Leibnitz monadic conception using the natural quanta (non-splitting e, π) along with their topological torsion in the form of dual isomorphism. The complete Euler’s identity controls a bounded regenerative/ recurrent multiverse (a kind of multigraph) by two regenerative exponential functions, one quantic, e = exp (1) and another gravitational, g0 ≡ 10 = exp (1) with the fixed points, g0 = π2 and (g0g0) respectively. Physically, the fixed points give the well-defined the unit gravity (g0 m/s2) and light self-ignition velocity of a stable recurrent self-sustained process, provided the rate of mass production just equals the rate removal. This is the Euler’s fictitious regenerative universe - like our world, a quantum autocatalytic reaction system. The present paper describes such a system controlled by thermal gravitational waves, in the case the critical solar system.